A comparison of different mask holds for positive pressure ventilation in a neonatal manikin. Issue 2 (16th October 2013) - Wilson, Emily V; O'Shea, Joyce E; Thio, Marta; Dawson, Jennifer A; Boland, Rosemarie; Davis, Peter G
Abstract : Background: Ventilation during neonatal resuscitation is typically initiated with a face mask, but may be ineffective due to leak or obstruction. Objective: To compare leak using three methods of mask hold. Methods: Medical and nursing staff regularly involved in neonatal resuscitation used the three holds (two-point, two-handed, spider) on a manikin in a random order to apply positive pressure ventilation (PPV) at standard settings each for 1 min while mask leak was recorded. Results: Participants (n=53) varied in experience (1–23 years) and hand size. Combined median (IQR) leak was 14 (2–46)% and was not different among the holds. Conclusions: There was no difference in the leak measured using the three different mask holds.